Effects of Grinding Process on the Properties of the Coal Bottom Ash and Cement Paste - Mangi, Sajjad Ali; Wan Ibrahim, Mohd Haziman; Jamaluddin, Norwati; Arshad, Mohd Fadzil; Memon, Sheeraz Ahmed; Shahidan, Shahiron (ITB Journal Publisher, LPPM ITB, 2019)
The grinding process is necessary to convert original coal bottom ash (CBA) into a powder form. The aim of this study is to evaluate the grinding process effects on physical properties of CBA, it influences on consistency and setting time of cement paste and to predict it potentiality based on chemical characteristics to reduce the alkali-silica reaction (ASR) in concrete. The CBA is the by-product of coal based thermal power plant. Due to high production of electricity in Malaysia, the excess amount of CBA has been produced annually and it causes the environmental problems. Therefore, it is necessary to come up with advanced solutions for that pollution. This study considered the different grinding periods i.e. 2, 10, 20, and 40hrs as to produce different particle fineness. It was perceived through the laboratory findings that the more the grinding period, finer the particle sizes. Besides that, cement paste with 10, 20 and 30% of ground CBA as a substitute of ordinary portland cement (OPC) by weight was prepared, it was observed that the consistency of OPC paste increases with the addition of ground CBA. Moreover, initial and final setting time of cement paste containing ground CBA was observed higher than the OPC paste. Hence, based on experimental analysis and energy efficiency scenario, grinding period of 20hrs with specific surface area 3835.75 cm2/g is suggested for the future studies.